Komunikasi Pemasaran Showroom Ridho Mobil dalam Memenuhi Kebutuhan Transportasi Pribadi Masyarakat di Kota Pematang Siantar - Ratna Bulan Damanik (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2026)
The development of digital technology has transformed marketing communication patterns in the automotive business, including used car showrooms in mid-sized cities. Ridho Mobil Showroom, as a used car trading business in Pematang Siantar City, is required to develop effective marketing communication strategies to meet the community's personal transportation needs. This study aims to determine how the marketing communication of Ridho Mobil Showroom fulfills the personal transportation needs of the community. A qualitative descriptive method was used, with data collected through in-depth interviews, observation, and documentation, and analyzed using the Miles and Huberman model comprising data reduction, data presentation, and conclusion drawing through source triangulation. The results show that Ridho Mobil Showroom has implemented an Integrated Marketing Communication (IMC) approach through the integration of five marketing communication mix elements: advertising via TikTok, Instagram, and Facebook; sales promotion through cash installment programs and discounts; consultative and educative personal selling; public relations based on business networking and word-of-mouth; and direct/digital marketing via WhatsApp and marketplace platforms. Digital marketing serves as the initial stimulus to attract consumer interest, while personal selling is the primary determinant of purchase decisions. The IMC integration strategy has effectively met the community's personal transportation needs, evidenced by efficient transaction processes, diverse unit availability, transparent vehicle condition information, and high consumer satisfaction.